A Cross Slot Coupling to Enhance Bandwidth of Dual-Layer SIW Structure - M. N. Hafiz; M. H. Jamaluddin; R. Selvaraju (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In this paper, design characteristics of cross slot coupling have been explored and realized in a proposed dual-layer SIW prototype for bandwidth enhancement at 10.0 GHz. The assembled prototype consists of two SMA-microstrip input/output interface with low-loss microstrip-taper via transition and two manually stacked SIW structures electrically connected via a small cross slot coupling design. The proposed dual-layer SIW structure is designed using CST software and fabricated using conventional Printed Circuit Board (PCB) manufacturing process on Rogers 4003 C with  = 3.38 and  = 0.813 mm. The close agreement between simulated and measured results is observed within a frequency range studied of 9.2 GHz to 11.2 GHz with 19.0 % bandwidth performance. The used of cross slot coupling design in the assembled dual-layer SIW structure indicated 9.0 % bandwidth enhancement compared to the conventional multilayer design with rectangular slot coupling. The assembled dual-layer SIW structure with cross slot coupling design shows potential in several RF applications such as radar and satellite communication.